Maternal Risk Factors Associated With Low Birth Weight Infants At Dr. M. Djamil Hospital, Padang (2023–2024) - Rahman, Chairani; Antonius, Puja Agung; Fitrayeni, Fitrayeni (Universitas Andalas, 2025)
The Infant Mortality Rate (IMR) in Indonesia remains higher than in developed countries, with one of the main contributing factors being Low Birth Weight (LBW) infants. The World Health Organization (WHO) reports that the global prevalence of LBW ranges from 15% to 20% of all births. In Indonesia, the prevalence of LBW based on the 2022 Indonesian Nutritional Status Survey (SSGI) was 6%, while in West Sumatra, the LBW rate was recorded at 4.4%. At Dr. M. Djamil Hospital Padang, data from 2023–2024 showed that the incidence of LBW reached 47.49% in 2023 and increased to 52.92% in 2024. LBW increases the risk of neonatal mortality by up to 20 times and has the potential to cause long-term complications. This study aims to analyze the relationship between maternal factors and low birth weight outcomes at Dr. M. Djamil Hospital, Padang, in 2023–2024. This research used a quantitative study design with a cross-sectional approach. The sample consisted of 58 postpartum mothers who met the inclusion criteria, selected using the Consecutive Sampling technique. The study found that 37.9% of newborns had LBW, 36.2% of mothers were either too young or too old, 37.9% were primiparous, 41.4% had preterm gestational age, and 39.7% experienced hypertensive disorders during pregnancy. Additionally, 43.1% of infants had severe asphyxia based on Apgar scores, 82.8% required NICU care, and 53.4% had comorbid asphyxia-related conditions. Bivariate analysis using the chi-square test showed significant associations between maternal age (p=0.018), parity (p=0.028), gestational age (p=0.024), and pregnancy morbidity (p=0.029) with LBW. There is a significant relationship between maternal age, parity, gestational age, and pregnancy morbidity with the incidence of low birth weight. Effective interventions are needed to reduce the prevalence of LBW and its associated complications. Low Birth Weight (LBW), Infant Mortality Rate (IMR), Maternal Factors, Neonatal Outcomes, Dr. M. Djamil Hospital Padang.